2000
DOI: 10.1038/sj.gt.3301242
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo transfection of plasmid DNA in the Dunning prostate tumor R3327-AT1 is enhanced by focused ultrasound

Abstract: Gene therapy as a form of molecular medicine is expected to have a major impact on medical treatments in the future. However, the clinical use of gene therapy today is hampered by inadequate gene delivering systems to ensure sufficient, accurate and safe DNA uptake in the target cells in vivo. Nonviral transfection methods might have the advantage of safe application, but it would be helpful to increase their transfection rates, especially in vivo. In this study, we show that focused ultrasound provides an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(93 citation statements)
references
References 35 publications
2
90
1
Order By: Relevance
“…Recently, the transfection efficiency of plasmid DNA was increased by ultrasound in cultured cells. [34][35][36] Consistent with previous reports, [34][35][36] the present study revealed a marked increase in transfection efficiency using ultrasound. Nevertheless, the degree of increased efficiency was still not enough.…”
Section: (B) Effect Of Transfection Of Human Hgf Plasmid On Number Ofsupporting
confidence: 93%
“…Recently, the transfection efficiency of plasmid DNA was increased by ultrasound in cultured cells. [34][35][36] Consistent with previous reports, [34][35][36] the present study revealed a marked increase in transfection efficiency using ultrasound. Nevertheless, the degree of increased efficiency was still not enough.…”
Section: (B) Effect Of Transfection Of Human Hgf Plasmid On Number Ofsupporting
confidence: 93%
“…Huber et al delivered a naked plasmid DNA reporter gene into subcutaneous Dunning prostate tumors in rats [76,77]. Insonation at 0.85 MHz produced a 10-fold to 15-fold increase in reporter activity compared to non-insonated controls.…”
Section: Tumor Tissuementioning
confidence: 99%
“…Although the ELISA test demonstrated increased gene expression after ultrasound, in the b-galactosidase staining, we could not detect b-gal-positive cells, presumably because of the low sensitivity of the X-gal staining procedure or a low protein expression per cell, which has been documented in earlier ultrasound studies. 23 Therefore, we were not able to assess transmural distribution of transgene expression. This discrepancy is a potential weakness of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonically induced heat elevation has not been reported to be an important mechanism of transfection induction, 23 while acoustic cavitation as a nonthermal phenomenon is considered to augment ultrasoundmediated transfection. 26,[29][30][31][32] Cavitation involves the formation of gaseous bubbles, a few micrometers in diameter, because of a disruption of the propagation medium by the negative pressure cycle in ultrasonic fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation